2013
DOI: 10.1021/sc4001077
|View full text |Cite
|
Sign up to set email alerts
|

s-Triazine Ring-Modified Waterborne Alkyd: Synthesis, Characterization, Antibacterial, and Electrochemical Corrosion Studies

Abstract: The surface coating industry is globally involved in developing useful, eco-friendly, and VOC (volatile organic compounds)-free coating systems, which exhibit promising physico-mechanical and corrosion protective performance. Herein, we report the synthesis of butylated melamine formaldehyde (BMF)-modified soy alkyd (SA-BMF). The structural elucidation and molecular weight of soy alkyd (SA) and SA-BMF resin was carried out by FT-IR, 1 H NMR, and 13 C NMR spectroscopy and gel permeation chromatography (GPC) tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 57 publications
1
82
0
Order By: Relevance
“…Alkyd resins based on non-toxic, biodegradable, multifunctional, low cost, physically and chemically stable and eco-friendly renewable resources such as vegetable oils show properties comparable with properties of products based on petroleum, and therefore have found their industrial application in paints and surface coatings [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Especially interesting low cost vegetable oil is soy bean oil, which has balanced composition of unsaturated and saturated fatty acids and it can reduce yellowing and oxidative degradation of resin [2,[16][17][18][19]. Araujo et al [16] have shown that anticorrosive properties of alkyd paints prepared with soy bean oil are similar to the anticorrosive properties of alkyd resins synthesized using linseed oil, but water vapor and ions permeability in freestanding film, as well as adhesion loss, depend on the type of pigment and vegetable oil used in the formulation of alkyd resins.…”
mentioning
confidence: 99%
“…Alkyd resins based on non-toxic, biodegradable, multifunctional, low cost, physically and chemically stable and eco-friendly renewable resources such as vegetable oils show properties comparable with properties of products based on petroleum, and therefore have found their industrial application in paints and surface coatings [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Especially interesting low cost vegetable oil is soy bean oil, which has balanced composition of unsaturated and saturated fatty acids and it can reduce yellowing and oxidative degradation of resin [2,[16][17][18][19]. Araujo et al [16] have shown that anticorrosive properties of alkyd paints prepared with soy bean oil are similar to the anticorrosive properties of alkyd resins synthesized using linseed oil, but water vapor and ions permeability in freestanding film, as well as adhesion loss, depend on the type of pigment and vegetable oil used in the formulation of alkyd resins.…”
mentioning
confidence: 99%
“…7,50,51 Characterisation Physicochemical properties of the resins such as iodine value, refractive index, specic gravity and inherent viscosity were determined by standard test methods (Table 1). The specimens were washed thoroughly with double distilled water, degreased with methanol and acetone, and dried at room temperature.…”
Section: Preparation Of Coatingsmentioning
confidence: 99%
“…Deionized water was used for the evaluation of the hydrophobic properties of the coated substrate. 7,50,51,53,54 The working electrode was rst maintained in a test environment for 30 min before the impedance run. The angle measurements were done in triplicate.…”
Section: Preparation Of Coatingsmentioning
confidence: 99%
“…Another nanomaterial, which is currently utilized as anticorrosive material, is the carbon dot (CD). CDs are the fluorescent class of nanomaterials consisting of several oxygenous groups having size below 10 nm . CD has been extensively explored due to its unique set of properties like excellent photocatalytic activity, low toxicity, and good biocompatibility .…”
Section: Introductionmentioning
confidence: 99%